Information Technology Asset Management System Web Based Application - Kamarudin, A'iniah (2005)
Information Technology (IT) has been widespread recently. Internet is a world network communication that links computers at homes, offices, institutions, universities, organizations and countries. It involves distance computing, electronic mail, file transfer and online forum. This research project is designed to create an online system for Bahagian Pengurusan Teknologi Maklumat, Jabatan Akauntan Negara Malaysia. The proposed online web application system will not only save time for resources in terms of tracking Information Technology Asset Management but also enhance the quality of services provided. This application will provide an unlimited online service for IT personnel and Jabatan Akauntan Negara employees. To implement the Information Technology Asset Management System web application. Image development tools, Hyper Text Markup Language (HTML), Java Script, and PHP Preprocessor Hypertext (PHP), and MySQL as database have to be used.